2013
DOI: 10.1002/adma.201303295
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube – Reduced Graphene Oxide Composites for Thermal Energy Harvesting Applications

Abstract: By controlling the SWNT-rGO electrode composition and thickness to attain the appropriate porosity and tortuosity, the electroactive surface area is maximized while rapid diffusion of the electrolyte through the electrode is maintained. This leads to an increase in exchange current density between the electrode and electrolyte which results in enhanced thermocell performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
191
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(195 citation statements)
references
References 29 publications
3
191
1
Order By: Relevance
“…16,17,30 In this work, the TEC properties were tested using a cup-shaped TEC and 0.4 M potassium ferro-ferricyanide aqueous solution was employed as the redox couple due to its high Seebeck coefficient. 2,7 As shown in Fig. 3a, the Seebeck coefficient was found to be $1.42 mV K À1 by linear tting of the data, which is in agreement with the previous reports.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…16,17,30 In this work, the TEC properties were tested using a cup-shaped TEC and 0.4 M potassium ferro-ferricyanide aqueous solution was employed as the redox couple due to its high Seebeck coefficient. 2,7 As shown in Fig. 3a, the Seebeck coefficient was found to be $1.42 mV K À1 by linear tting of the data, which is in agreement with the previous reports.…”
supporting
confidence: 80%
“…Romano et al reported that the TEC performances of single-walled carbon nanotube-reduced graphene oxide hybrid electrodes were improved signicantly due to an enhanced mass transport property. 7 Im et al reported that decorating CNTs with Pt nanoparticles (NPs) could result in much higher conversation efficiency in comparison with pristine CNTs due to faster kinetics and larger electroactive sites.…”
Section: 3mentioning
confidence: 99%
“…Ferricyanide and ferrocyanide represent a common redox couple utilised in thermogalvanic cells [4]. Reduction of ferrocyanide to ferricyanide results in a net increase in entropy [5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they were considered for the liquid phase exfoliation of graphite to graphene in the current study. In addition, cyclohexyl-pyrrolidone (CHP), which was found to be the most efficient solvent for the debundling of single walled carbon nanotubes (SWNTs) (surface tension of 38.8 mJ/m2) [62,63] was also considered for the solvent exfoliation process. Figure 1b shows EG dispersions in CHP, DMF and NMP after 8 h bath sonication.…”
Section: Solvent Exfoliation Of Graphitementioning
confidence: 99%